The Implication of Gastric Microbiome in the Treatment of Gastric Cancer - George Pappas-Gogos (Cancers, 2022)
Gastric cancer (GC) is one of the most common and deadly malignancies worldwide. Helicobacter pylori have been documented as a risk factor for GC. The development of sequencing technology has broadened the knowledge of the gastric microbiome, which is essential in maintaining homeostasis. Recent studies have demonstrated the involvement of the gastric microbiome in the development of GC. Therefore, the elucidation of the mechanism by which the gastric microbiome contributes to the development and progression of GC may improve GC’s prevention, diagnosis, and treatment. In this review, we discuss the current knowledge about changes in gastric microbial composition in GC patients, their role in carcinogenesis, the possible therapeutic role of the gastric microbiome, and its implications for current GC therapy.